Non-aggregated Zn(ii)octa(2, 6-diphenylphenoxy) phthalocyanine as a hole transporting material for efficient perovskite solar cells1. Issue 23 (21st June 2015) - Javier Ramos, F.; Ince, M.; Urbani, M.; Abate, Antonio; Grätzel, M.; Ahmad, Shahzada; Torres, T.; Nazeeruddin, Mohammad Khaja
<x xml:space="preserve">Abstract</x> A non-aggregated Zn(ii)octa(2, 6-diphenylphenoxy) phthalocyanine (coded as TT80) has been used as a hole-transporting material for perovskite solar cells.